Tourism Innovation Based on Virtual Ecotourism Technology at Tangkahan Ecopark - Destiadi, Rezha; Chan, Andi Supriadi; Hasibuan, Annalisa Sonaria (International Journal of Research in Vocational Studies (IJRVOCAS), 2024)
Saving the environment or nature conservation as a journey is an activity that has become an option for developing tourism. Tangkahan Ecopark is one of the tourist attractions in the interior that is engaged in sustainable tourism and increasing ecological and recreational values. This research is limited to the observation area, namely the Tangkahan Ecopark Area. This research produces an implementation design based on virtual reality ecotourism technology in Tangkahan Ecopark tourism using a mixed method through an MDLC development design, data analysis based on the results of interviews, observations and literature studies. The output must be a tourism design model based on virtual ecotourism technology and Intellectual Property from the virtual technology device.